Photo-texts : contemporary French writing of the photographic image - Stafford, Andy (Contemporary French and francophone cultures, 2010)
Taking nine case studies from the French-speaking world, this book attempts to define the interaction between non-fictional written text (caption, essay, fragment, poem) and photographic image. Considering three categories of intermediality between text and photography the book concludes that the dimensions of their interaction are complex.